Effect of Media Type and Storage Duration on Viability of Cocoa (Theobroma cacao L.) Seeds - Abdul Rahman; Syahbudin Hasibuan; Dwika Karima Wardani; Agus Ardi (International Journal of Engineering, Science and Information Technology, 2022)
This study aims to determine the best storage media and storage time for cocoa seeds. The research was carried out at the Plant Physiology Laboratory, Faculty of Agriculture, Medan Area University. The analytical method used is Completely Randomized Design (CRD) with treatments, namely No Storage Media, Use of PE Plastic Storage Media + 1 Week Storage, PE Plastic + 2 Weeks Storage, PE Plastic + 3 Weeks Storage, Aluminum Foil Paper + 1 Week Storage, Aluminum Foil + 2 Weeks Storage, Aluminum Foil Paper + 3 Weeks Storage, Burlap Sack + 1 Week Storage, Burlap Sack + 2 Weeks Storage, Burlap Sack + 3 Weeks Storage, Glass Bottle + 1 Week Storage, Glass Bottle + 2 Weeks Storage , Glass Bottle + 3 Weeks of Storage, a total of 12 treatments with 3 replications. The data were analyzed statistically with the F test at a 5% significance level. If F Count is greater than F Table 5%, then it is continued with the Duncan' New Multiple Range Test (DNMRT) at a level of 5%. The results showed that the treatment on several storage media had a significant effect on the simultaneous growth of cocoa seeds. And the length of time for storing seeds for one week was significantly different, there were parameters for observing seed germination, seed growing simultaneously and seed growing speed.